Urinary NGAL as a Diagnostic and Prognostic Marker for Acute Kidney Injury in Cirrhosis: A Prospective Study. Issue 5 (11th May 2021) - Allegretti, Andrew S.; Parada, Xavier Vela; Endres, Paul; Zhao, Sophia; Krinsky, Scott; St. Hillien, Shelsea A.; Kalim, Sahir; Nigwekar, Sagar U.; Flood, James G.; Nixon, Andrea; Simonetto, Douglas A.; Juncos, Luis A.; et al.
Abstract : INTRODUCTION: Urinary neutrophil gelatinase-associated lipocalin (NGAL) has shown promise in differentiating acute tubular necrosis (ATN) from other types of acute kidney injuries (AKIs) in cirrhosis, particularly hepatorenal syndrome (HRS). However, NGAL is not currently available in clinical practice in North America. METHODS: Urinary NGAL was measured in a prospective cohort of 213 US hospitalized patients with decompensated cirrhosis (161 with AKI and 52 reference patients without AKI). NGAL was assessed for its ability to discriminate ATN from non-ATN AKI and to predict 90-day outcomes. RESULTS: Among patients with AKI, 57 (35%) had prerenal AKI, 55 (34%) had HRS, and 49 (30%) had ATN, with a median serum creatinine of 2.0 (interquartile range 1.5, 3.0) mg/dL at enrollment. At an optimal cutpoint of 244 μg/g creatinine, NGAL distinguished ATN (344 [132, 1, 429] μg/g creatinine) from prerenal AKI (45 [0, 154] μg/g) or HRS (110 [50, 393] μg/g; P < 0.001), with a C statistic of 0.762 (95% confidence interval 0.682, 0.842). By 90 days, 71 of 213 patients (33%) died. Higher median NGAL was associated with death (159 [50, 865] vs 58 [0, 191] μg/g; P < 0.001). In adjusted and unadjusted analysis, NGAL significantly predicted 90-day transplant-free survival ( P < 0.05 for all Cox models) and outperformed Model for End-Stage Liver Disease score by C statistic (0.697 vs 0.686; P = 0.04), net reclassification index (37%; P = 0.008), and integrated discrimination increment (2.7%; P = 0.02). DISCUSSION: NGAL differentiates the type of AKI in cirrhosis and may improve prediction of mortality; therefore, it holds potential to affect management of AKI in cirrhosis.